2020
DOI: 10.3390/nu12092710
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Indigenous Diet Iron Content and Location on Hemoglobin Levels of Ghanaians

Abstract: Multiple studies have demonstrated strong links between diet and anemia, but few have explored the impact of food groups on hemoglobin (Hb). We analyzed the correlation between Ghanaian diet and Hb levels to explore reduction of anemia prevalence through dietary interventions. Demographics, food frequency questionnaires (FFQ), and blood samples were obtained from 140 volunteers (ages 18–65) in five locations across Ghana. Hb was measured; estimated iron consumption was calculated. FFQ items were grouped by foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…A study conducted in Ghana showed that animal foods per calorie have a higher influence on hemoglobin levels [21]. However, a typical Ghanaian diet is chiefly carbohydrate with little animal protein.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Ghana showed that animal foods per calorie have a higher influence on hemoglobin levels [21]. However, a typical Ghanaian diet is chiefly carbohydrate with little animal protein.…”
Section: Discussionmentioning
confidence: 99%